Strong Convegence Theorems for General Equilibrium Problems and Fixed Point Problems in Banach Spaces: Uthai Kamraksa, Chaichana Jaiboon - Team, Support (Thai Journal of Mathematics, 2015)
In this paper, we introduce an itertive scheme for finding a common element of the of solution of the general equilibrium problem and the set fixed point of nonexpansive mappings in Banach space. Under suitable conditions, some strong convergence theorem for approximating a common element of the above two sets are obtained. Results obtained in this paper improve the previously known results in this area.